Proenkephalin and risk of developing chronic kidney disease: the Prevention of Renal and Vascular End-stage Disease study. (4th July 2018) - Kieneker, Lyanne M.; Hartmann, Oliver; Bergmann, Andreas; de Boer, Rudolf A.; Gansevoort, Ron T.; Joosten, Michel M.; Struck, Joachim; Bakker, Stephan J. L.
Abstract: Background: Proenkephalin (pro-ENK) was recently found to be associated with low estimated glomerular filtration rate (eGFR). The association of pro-ENK with urinary albumin excretion (UAE), another marker for chronic kidney disease (CKD), has not been investigated. We examined the association of pro-ENK with eGFR and UAE as markers of CKD. Methods: We included 4375 subjects of the Prevention of Renal and Vascular End-Stage Disease (PREVEND) study. CKDeGFR was defined as development of eGFR <60 ml/min/1.73 m 2 and CKDUAE as albuminuria >30 mg/24 h. Results: Baseline median pro-ENK was 52.2 (IQR: 44.9–60.5) pmol/L. After a median follow-up of 8.4 (IQR: 7.9–8.9) years, 183 subjects developed CKDeGFR and 371 developed CKDUAE . The association of pro-ENK with CKDeGFR was modified by sex ( P interaction  < 0.1), in such a way that after adjustment, the association only remained significant in men (adjusted hazard ratio per SD increase in 10 log-transformed pro-ENK, 1.65; 95% CI: 1.15–2.36) and not in women (0.83; 0.58–1.20). No significant association was observed between pro-ENK and CKDUAE risk (0.83; 0.58–1.20). Conclusions: High pro-ENK is associated with increased risk of CKDeGFR in men, but not in women. No association of pro-ENK with CKDUAE was observed. These results should be interpreted with caution, since residual confounding and potential overfitting of models could have influenced the results.